The Influence of Principals' Problem-Solving Competence on Teacher Performance - Rahmawati, Firda Dwi; Abdushomad, Adib; Acharjya, Vasavvi; Gisthi, Sinta (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to analyze the influence of principal problem-solving competence on teacher performance. The method used is quantitative with ex-post facto design and correlation and regression approaches. Data were collected through questionnaires and analyzed using SPSS version 17. Samples were taken randomly from 181 teachers. The collected data were analyzed mathematically. The results showed that principal problem-solving competence positively and significantly correlated with teacher performance (correlation value 0.608 or 60.8%). There is a direct influence of 28%, an indirect influence of 13%, and a total influence of 41% from problem-solving competence on teacher performance. Based on these findings, improving teacher performance is greatly influenced by the principal’s competence in problem-solving. The study's implications indicate that to improve teacher performance, principals must have skills in dealing with and solving problems. Therefore, training in problem-solving for principals is essential to improve the quality of education.